Influence of geographical and genetic variation on GABA content in Annona muricata grown in Thailand - Deewatthanawong, R.; Tontiworachai, B.; Kongchinda, P.; Chanapan, S.; Sriwilaiwan, S.; Deewatthanawong, P.; Montri, N. (My University, 2020)
Annona is a genus of tropical fruit trees in the family Annonaceae. Fruit pulp of Annona muricata contained the highest amount of gamma-aminobutyric acid (GABA) among Annona species. GABA content results from many factors including genetic makeup and environment. Influences of genetic variation and geographical environment on GABA content in fruit pulp of A. muricata were determined. To study genetic variation, sequences of ITS2 and psbA-trnH were used to construct phylogenetic trees. Young leaves of A. muricata were collected from different geographical locations including Chumphon, Trang, Nakhon Ratchasima, Nakhon Si Thammarat, Buriram, Nong Khai, Udon Thani, and Prachuap Khiri Khan Provinces in Thailand. Sequences of ITS2 and psbA-tmH were aligned and data sets were analyzed using maximum likelihood (ML) and neighbor-joining (NJ) methods. ITS2 sequence variations were observed within and among samples from different locations. A. muricata fruit harvested from eight provinces, namely Chumpon, Trang, Nakhon Ratchasima, Nakhon Si Thammarat, Buriram, Nong Khai, Udon Thani, and Prachuap Khiri Khan contained 19.75, 35.02, 32.91, 28.18, 42.37, 32.17, 65.02, and 31.58 mg 100 g-1 FW GABA, respectively. Findings indicated that both geographical environment and genetic variation had significant effects on GABA content in A. muricata fruit.
Keywords: Gamma-aminobutyric acid; Geographical environment; Phylogenetic analysis; Soursop